On the uniqueness of the mixed equilibrium in the Tullock contest - Christian Ewerhart (University of Zurich, Department of Economics, 2024)
It is shown that the two-player Tullock contest admits precisely one equilibrium in randomized strategies.
Keywords: C72; D72; 330; Tullock contest; mixed equilibrium; sequence spaces; Cauchy matrices; Dirichlet series